Gas permeation behavior of phenolphthalein based heat-resistant polymers PEK-C and PES-C - Liu, W.; Chen, T.; Xu, J.
Polyarylether ketone and polyarylether sulfone contammg a cardo group (PEK-C and PES-C)are newly synthesized heat-resistant polymers This paper presents the permeation rate data of eight gases through PEK-C and PES-C membranes on a laboratory-made low vacuum manometnc apparatus capable of measurmg m a mde temperature range (25-160°C ) Apparent actwatlon enermes of permeation for the eight gases are calculated The prospect of apphcatlon of the membrane mater& for H2/N2, H&O and CO&H, separations at high temperature 1s discussed A distinct change m slope of the Arrhemus plots 1s observed for most gases through PEK-C near 68 ' C, showmg the existence of a transltlon, which 1s further confirmed by other charactenzatlon methods